2018
DOI: 10.1038/s41538-018-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Extensional and shear rheology of okra polysaccharides in the presence of artificial saliva

Abstract: Extensional and shear viscosities were studied for mixtures comprising artificial saliva and okra mucilage, the latter acting as a model thick-liquid food. These experiments aimed to obtain information on the flow-behavior information of the systems, underpinning the texture sensation of foods as perceived by dysphagic and xerostomic populations. Mixing okra mucilage with artificial saliva dramatically increases the shear viscosity of artificial saliva throughout the studied ranges of concentrations and deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Extensional deformation occurs when a stress is applied perpendicularly to the surface of the deformation (Lv, Chen, & Holmes, 2017), as in the up‐down (munching) oral processing method. Extensional flow may cause much higher deformations in colloidal systems in comparison with shear deformation (Yuan, Ritzoulis, & Chen, 2018). Furthermore, Lv et al (2017) have found that humans have a greater discriminatory capacity in perceiving extensional compared to shear viscosity, even though the mechanisms are not understudied (Yuan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensional deformation occurs when a stress is applied perpendicularly to the surface of the deformation (Lv, Chen, & Holmes, 2017), as in the up‐down (munching) oral processing method. Extensional flow may cause much higher deformations in colloidal systems in comparison with shear deformation (Yuan, Ritzoulis, & Chen, 2018). Furthermore, Lv et al (2017) have found that humans have a greater discriminatory capacity in perceiving extensional compared to shear viscosity, even though the mechanisms are not understudied (Yuan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Extensional flow may cause much higher deformations in colloidal systems in comparison with shear deformation (Yuan, Ritzoulis, & Chen, 2018). Furthermore, Lv et al (2017) have found that humans have a greater discriminatory capacity in perceiving extensional compared to shear viscosity, even though the mechanisms are not understudied (Yuan et al, 2018).…”
Section: Linking the Rheological Sensory And Nutritive Properties Of ...mentioning
confidence: 99%
“…[63] The mucilage of the okra is composed of up to 70% polysaccharides. [64,65] The okra gel is rich in acidic polysaccharides, [66] including galactose, rhamnose, and galacturonic acid, and their partially acetylated form. [67] However, okra gel as a hemostatic bioadhesive has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies on extensional rheology, although synthetic polymers were used as a test specimen in most cases in the past, studies on food polymers increase recently using a capillary breakup extensional rheometer (CaBER). These include casein and starch (Chan et al, 2007), guar gum (GG; Duxenneuner, Fischer, Windhab, & Cooper‐White, 2008; Torres, Hallmark, & Wilson, 2014), xanthan gum and carboxymethyl cellulose (CMC) (Choi, Mitchell, Gaddipati, Hill, & Wolf, 2014), and okra viscous extraction (Yuan, Ritzoulis, & Chen, 2018). Usefulness of extensional viscosity has been validated for evaluating mechanical or rheological properties of dysphagia thickeners (Hadde & Chen, 2019; Nishinari, Turcanu, Nakauma, & Fang, 2019; Waqas, Wiklund, Altskär, Ekberg, & Stading, 2017).…”
Section: Introductionmentioning
confidence: 99%